MENINGKATKAN KEMAMPUAN KOGNITIF DALAM PEMBELAJARAN E-LEARNING MELALUI MODEL MAKE A MATCH UNTUK ANAK USIA DINI DI KELOMPOK A - Erna Nuryani; Chandra Asri Windarsih; Syah Khalif Alam (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2022)
The cognitive abilities of group A children in Kober Asy-Syukriyah are still very low, this is because the selection of the learning model used by the teacher does not attract children's attention. Coupled with the current learning conditions that are carried out online, so that learning is carried out through e-learning. The use of creative and innovative learning models is needed to increase students' attention. One of the appropriate e-earning learning models to move children to be able to think, reason, seek and find answers is the make a match model. The purpose of this study is to describe scenarios and implementation of e-learning learning in improving cognitive abilities through the make a match model. The research method used in this research is a descriptive qualitative research method. The subjects in the study consisted of eight (8) men and two (2) women so that there were 10 people. Data were collected through observation sheets, interview instruments and documentation. Data analysis is in the form of data reduction activities, data display and drawing conclusions. Based on the results of the study, there was an increase in the cognitive abilities of group A children in Kober.Kemampuan kognitif anak kelompok A di Kober Asy-Syukriyah masih sangat rendah hal itu dikarenakan pemilihan model pembelajaran yang digunakan guru kurang menarik perhatian anak. Ditambah dengan kondisi pembelajaran sekarang yang dilaksanakan secara daring, sehingga pembelajaran dilaksanakan melalui e-learning. Penggunaan model pembelajaran yang kreatif dan inovetif dibutuhkan untuk meningkatkan perhatian siswa. Salah satu model pembelajaran e-earning yang tepat untuk  menggerakan anak agar mampu berpikir, menalar, mencari dan menemukan jawaban ialah model make a match. Tujuan penelitian ini ialah untuk mendeskripsikan skenario dan implementasi pembelajaran e-learning dalam meningkatkan kemampuan kognitif melalui model make a match. Metode penelitian yang digunakan dalam penelitian adalah metode penelitian kualitatif yang bersifat deskriptif. Subjek dalam penelitian terdiri dari delapan (8) orang laki-laki dan dua (2) orang wanita segingga berjumlah 10 orang. Data dikumpulkan melalui lembar observasi, instrumen wawancara dan dokumentasi. Analisis data berupa aktifitas reduksi data, display data dan penarikan kesimpulan. Berdasarkan hasil penelitian terdapat peningkatan kemampuan kognitif anak kelompok A di Kober Asy-Syukriyah.